Using Communicative Language Teaching to improve speaking skills of Brazilian EFL young adult students - Loebens, Rafael (My University, 2019)
This paper aims to suggest ways the Communicative Language Teaching could be used to improve fluency and pronunciation of Brazilian students of English as a Foreign Language. From the observation of difficulties faced by Brazilians when speaking English, regarding fluency and some specific aspects of pronunciation, it was noticed the need for proposing ideas to try to improve those aspects. The characteristics of the speaking issues faced by Brazilians, principles of Communicative Language Teaching and features involved in speaking skills were analyzed. In the sequence, some examples of communicative activities were suggested followed by commentary by the author. It is hoped the suggestions can be useful for English teachers in Brazil, however a research with data collection would be needed to make the point conclusive (sic).
Esse artigo tem como objetivo sugerir formas em que o ensino comunicativo de idioma poderia ser usado para melhorar a fluência e pronúncia de brasileiros estudantes de língua inglesa como língua estrangeira. A partir de observações das dificuldades encontradas por brasileiros ao falar inglês, em relação à fluência e alguns aspectos específicos da pronúncia, notou-se a necessidade de se propor ideias para tentar melhorar esses aspectos. Analisaram-se as características de problemas da fala de inglês por brasileiros, os princípios do ensino comunicativo de idioma e aspectos envolvidos nas habilidades de fala. Na sequência, alguns exemplos de atividades comunicativas foram sugeridas acompanhadas de comentários pelo autor. Espera-se que as sugestões possam ser úteis para professores no Brasil, entretanto uma pesquisa com coleta de dados seria necessário para fazer esse ponto conclusivo (sic).
Keywords: Teaching; Speech; Fluency (Language learning); English language - Pronunciation